Exploring Career Indecision among Indonesian High School Students: A Rasch Model Insight - Siti Aminah; Caraka Putra Bhakti; Rozita Jayuz; Ari Khusumadewi; Husni Abdillah (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Career indecision is a prevalent issue among high school students, significantly impacting their ability to make informed career choices.This study aimed to investigate the factors that contribute to high school students' career indecision. This study included 413 high school students from the Special Region of Yogyakarta, Central Java, and East Java. The information was gathered using the Career Decision Scale (CDS). The findings of this study indicate that the level of career indecision experienced by students varies significantly between individuals and is strongly influenced by the demographic variables examined in this study. This study also confirmed that all of the students had difficulty deciding on a future career path. In this article, demographic differences in the percentage of high school students who are unsure about their future careers are also discussed.These findings highlight the need to enhance career counseling services and establish comprehensive support systems to help high school students navigate career decision-making. Integrating family into career counseling supports students' exploration of interests and values, while expanding opportunities and a supportive environment strengthen decision-making and reduce career indecision.